A potential zero water exchange system for recirculating aquarium using a DHS-USB system coupled with ozone. Issue 2 (15th January 2022) - Adlin, Nur; Hatamoto, Masashi; Yamazaki, Shinichi; Watari, Takahiro; Yamaguchi, Takashi
ABSTRACT: Partial water exchange is one of the most common conventional methods used to maintain water quality and aesthetic beauty in recirculating aquarium systems (RASs). However, this method uses substantial amount of water. The ozone-down-flow hanging sponge-up-flow sludge blanket (ozone-DHS-USB) system attempts to be a more responsible method for aquarium maintenance. It eliminates the necessity for water exchange in aquarium by maintaining nitrogen concentrations at a safe level and by reducing yellow substances. Also, the impact of O3 on the DHS-USB system was investigated. The system was assayed using an on-site freshwater aquarium influenced by ambient temperature ranging from 23°C to 34°C. During ozonation Phases 1 and 3, the colour of the water in the aquarium was successfully maintained below 10 colour units. The 16S rRNA gene analysis of microorganisms in the DHS revealed that constant application of O3 has caused a decrease in nitrite-oxidizing bacteria (NOB). Nevertheless, NH3 and NO 2 − were maintained within 0.1 mg N L −1, and NO 3 − was maintained at 14.6 ± 9.20 mg N L −1 throughout the study. Carps survived for 425 days without any water exchange performed. Our study supports that the ozone-DHS-USB system has a high potential towards creating low-maintenance aquaria. GRAPHICAL ABSTRACT: UF0001